Financial Behavior and Financial Technology: A Case Study of Peer-To-Peer Lending - Estu Widarwati; Nunik Nurmalasari; Moeljono; Arizal Hamizar; Ahmad Arif Zulfikar; E. Wityasminingsih (Business Review and Case Studies, 2024)
Background: A digital-based economy is one of the pillars of economic growth and per capita income. Financial Technology (Fintech), which adapts technological change combined with the financial sector, is expected to introduce a more instant, convenient, and modern financial transaction process. Purpose: This study examined the influence of financial behavior due to Fintech Lending (Peer-to-Peer Lending/P2P), focusing on respondents who had made fintech lending loans. Design/methodology/approach: The research approach used an explanatory survey with a sample of 132 respondents from several regions of Indonesia. Data collection was conducted using an online questionnaire distributed via the GF link during the period of 2022-2023. The data were processed by testing data quality, including validity testing, reliability testing, and classic assumption testing.Findings/Result: The study showed that individuals with higher incomes tended to take out loans, with the majority using these loans for business capital, daily needs, debt payments, and consumption. Financial behavior significantly impacted fintech lending, highlighting the importance of personal financial management to minimize fintech risks, particularly those associated with online loans (P2P).Conclusion: It needs to be a government concern to carry out better financial literacy so that people understand the risks of fintech lending, in this case, online loans (P2P).Originality/value (State of the Art): Personal financial behavior becomes a main determinant in personal fintech lending management. Keywords: financial behaviour, fintech, risk, peer to peer lending, Indonesia